The use of a high‐power (50 W), ablation index‐guided protocol for ablation of the cavotricuspid isthmus. Issue 6 (8th October 2020) - Tscholl, Verena; Kamieniarz, Paul; Nagel, Patrick; Landmesser, Ulf; Attanasio, Philipp; Huemer, Martin
Abstract: Background: High‐power (HP) ablation protocols are increasingly used for ablation procedures to shorten procedural times and improve short‐ and long‐term success. The ablation index (AI) combines contact force, power settings, and ablation time. It can be used in combination with HP protocols to guide operators toward standardized lesions. The purpose of this study was to evaluate both a HP and AI‐guided strategy for ablation of the cavotricuspid isthmus (CTI) in patients with typical atrial flutter (AFL). Methods: In this single‐center study, consecutive patients with typical AFL (n = 52, mean age 68.7 ± 8.3 years, 21/52 [40.4%] female) underwent AI‐guided HP radiofrequency (RF) ablation of the CTI. Ablation was performed with 50 W and AI target values of 550 with a maximum ablation duration of 25 seconds per lesion. Target interlesion distance was ≤6 mm. Ablation was performed with a 3.5 mm porous tip Smarttouch SF catheter. Results: Acute CTI block was achieved in 52 of 52 patients (100%), and first‐pass conduction block was achieved in 41 of 52 patients (80.4%). Spontaneous reconduction after 30 minutes waiting time occurred in 1 of 52 (1.9%) patient. Average ablation time until CTI block was 3:51 ± 1:40; 2:33 ± 1:01 minutes of bonus ablation pulses were applied after CTI block. An audible steam pop was noted in one patient (1.9%). No major complications occurred. After a mean follow‐up of 193.7 ± 152.2 days, no patient showed recurrence of typical AFL. Conclusion: In this pilot study, AI‐guided HP ablation of the CTI was fast, safe, and effective. Abstract : In this single‐center, prospective pilot study we demonstrated in 52 patient, that an Ablation Index Guided, High Power Ablation of the Cavotricuspid Isthmus in Patients with typical atrial flutter is fast, safe and effective. CTI Block was achieved in 3:51 ± 1:40 minutes of average ablation time. First pass conduction block was achieved in 80.4%. No patient showed recurrence of typical atrial flutter. No major complications occured.